SEISMICITY CHANGES DETECTION DURING THE SEISMIC SEQUENCES EVOLUTION AS EVIDENCE OF STRESS CHANGES - Astiopoulos, A.C.; Papadimitriou, E.; Karakostas, V.; Gospodinov, D.; Drakatos, G. (Bulletin of the Geological Society of Greece, 2010)
The statistical properties of the aftershock occurrence are among the main issues in investigating the earthquake generation process. Seismicity rate changes during a seismic sequence, which are detected by the application of statistical models, are proved to be precursors of strong events occurring during the seismic excitation. Application of these models provides a tool in assessing the imminent seismic hazard, oftentimes by the estimation of the expected occurrence rate and comparison of the predicted rate with the observed one. The aim of this study is to examine the temporal distribution and especially the occurrence rate variations of aftershocks for two seismic sequences that took place, the first one near Skyros island in 2001 and the second one near Lefkada island in 2003, in order to detect and determine rate changes in connection with the evolution of the seismic activity. Analysis is performed through space–time stochastic models which are developed, based upon both aftershocks clustering studies and specific assumptions. The models applied are the Modified Omori Formula (MOF), the Epidemic Type Aftershock Sequence (ETAS) and the Restricted Epidemic Type Aftershock Sequence (RETAS). The modelling of seismicity rate changes, during the evolution of the particular seismic sequences, is then attempted in association with and as evidence of static stress changes